ANALISIS REAKSI PASAR SAHAM PADA PENGUMUMAN DAFTAR EMITEN INDEKS LQ45 DI BURSA EFEK INDONESIA - Suryadi Samudra; Surayya Surayya; Abdul Kadir; Akhmad Akhmad (Jurnal Ekonomi Trend, 2023)
This study aims to analyze the market reaction in the Indonesia Stock Exchange to the announcement of the list of companies in the LQ45 index. The research methodology used in this study is event study., which involves calculating and analyzing the abnormal returns obtained by the newly added companies during the announcement period. The population for this study consists of companies listed in the LQ45 index, with a sample of 25 companies from 2019 to 2022. Statistical analyses utilized include One Sample T-Test to examine the differences in abnormal returns on a daily basis during the event period, and Wilcoxon Signed-rank Test to compare the differences in abnormal returns before and after the announcement. The results of the statistical analysis indicate a significant positive abnormal return on the first day following the announcement, followed by a subsequent market adjustment resulting in no further significant abnormal returns. Furthermore, there were no significant differences in abnormal returns before and after the announcement, indicating a rapid market response in adjusting prices. Keywords: Stock market reaction, event study, LQ45 index announcement, abnormal return